Colored & alive - Bento, Oluwa Seyi Salles (Revista Interseção, 2026)
RESUMO: Este Poema foi apresentado no IV Seminário Nacional do NUDES, I Seminário Internacional do NUDES: Sociedade, Educação e Direitos Humanos: equidade na diversidade. PALAVRAS-CHAVE: Contar. Recordar. Vida. ABSTRACT: This poem was presented at the IV National Seminar of NUDES, I International Seminar of NUDES: Society, Education and Human Rights: equity in diversity. KEYWORDS: Counting. Remembering. Life. Para Ntozake Shange, quem me recordou que o arco-íris é um Orixá